A feasibility study of percutaneous transhepatic gallbladder filling (PTGBF) in a swine model. Issue 7 (3rd October 2022) - Ogawa, Yukihisa; Kubota, Manabu; Takagi, Masayuki; Mimura, Hidefumi
Abstract: Background: Treatments for acute cholecystitis include cholecystectomy and percutaneous drainage. However, some patients are at high risk for surgery, and prolonged drainage can decrease their quality of life. Purpose: To determine the feasibility of percutaneous transhepatic gallbladder filling (PTGBF) with n-butyl-cyanoacrylate (NBCA) in a swine model. Material and methods: After the induction of general anesthesia, percutaneous transhepatic gallbladder puncture to a pig weighing 49 kg using a 20-G-percutaneous transhepatic cholangio drain (PTCD) needle was performed under ultrasound guidance. A 2.1 F-microcatheter was inserted through the outer PTCD needle, then the cystic duct was coil-embolized. The microcatheter was removed, the gallbladder was filled with 25% NBCA-Lipiodol, then the PTCD needle was withdrawn without complications. Blood was sampled and CT images were acquired from the pig immediately after the procedure and on postoperative day 7. The pig was euthanized on postoperative day 7 and the gallbladder was evaluated by microscopy. Results: Vital signs were stable, and the CT images showed that the gallbladder contained NBCA-Lipiodol without complications such as leakage. Hepatobiliary enzymes were not elevated. Histological findings demonstrated loss of most mucosa with partial regeneration, and lymphocytic infiltration. The muscle layer was intact. Conclusion: This technique might offer a feasible alternative to surgery for high-risk patients with acute cholecystitis, but further studies are needed to determine the safety and long-term effects of this procedure.